2005
DOI: 10.1080/09500690500069483
|View full text |Cite
|
Sign up to set email alerts
|

Scientific knowledge and attitude change: The impact of a citizen science project

Abstract: This paper discusses the evaluation of an informal science education project, The Birdhouse Network (TBN) of the Cornell Laboratory of Ornithology. The Elaboration Likelihood Model and the theory of Experiential Education were used as frameworks to analyse the impact of TBN on participants' attitudes toward science and the environment, on their knowledge of bird biology, and on their understanding of the scientific process. The project had an impact on participants' knowledge of bird biology. No statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
438
4
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(471 citation statements)
references
References 22 publications
22
438
4
7
Order By: Relevance
“…Many projects are explicitly designed to have citizen scientists experience the scientific processes; thus, Bonney et al [2009] concluded that most citizen-science projects are designed to help citizen scientists learn scientific knowledge to some degree. Consistent with these efforts, volunteers of citizen-science projects reported that they actually learned about science by participating in the projects [e.g., Brossard, Lewenstein and Bonney, 2005;Land-Zandstra et al, 2016a;Masters et al, 2016].…”
Section: Learning About Sciencementioning
confidence: 81%
See 2 more Smart Citations
“…Many projects are explicitly designed to have citizen scientists experience the scientific processes; thus, Bonney et al [2009] concluded that most citizen-science projects are designed to help citizen scientists learn scientific knowledge to some degree. Consistent with these efforts, volunteers of citizen-science projects reported that they actually learned about science by participating in the projects [e.g., Brossard, Lewenstein and Bonney, 2005;Land-Zandstra et al, 2016a;Masters et al, 2016].…”
Section: Learning About Sciencementioning
confidence: 81%
“…The possibility to contribute to science has emerged as a major motivation in several studies. For example, Zooniverse volunteers answered that they are more motivated by their contribution to science than by the possibility to learn about science or to help scientists [Brossard, Lewenstein and Bonney, 2005;Reed et al, 2013]. Contributing to science was listed as a primary contributor for participation in CosmoQuest [Gugliucci, Gay and Bracey, 2014], Foldit [Curtis, 2015], and in the Dutch Great Influenza Survey [Land-Zandstra et al, 2016b] and the second most cited reason for the Great Pollinator Project [Domroese and Johnson, 2017].…”
Section: Contributing To Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the attitude evaluation using observation sheet is needed, to get an accurate measurement. A proper and accurate measurement tool to evaluate the change in one's attitude is also argued by Brossard et al (2005). That is why the present research also employed observations to measure students' attitudes towards the environment.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Citizen science will usually incorporate an element of public education [2,6,[13][14][15]. Silvertown [5] described the differentiation between historical and modern forms of citizen science by potential for it to be "available to all, not just a privileged few."…”
Section: Introductionmentioning
confidence: 99%